Croatian language resources for NooJ - Kocijan, Kristina; Bekavac, Božo; Tadić, Marko (2010)
This paper presents the Croatian module for NooJ. The module includes Croatian author Vjenceslav Novak and his novel 'Posljednji Stipančići' as a corpus with fully covered dictionary (i.e. zero unknowns). Examples of morphological and syntactic grammars are included together with few examples of dictionary entries and their inflectional and derivational paradigms
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG